A new endemic Synagapetus species (Trichoptera: Glossosomatidae) from Madeira Island (Portugal) - Martín, Luis; Martínez, Jesús; Aguín-Pombo, Dora; González, Marcos A. (Zootaxa, 2017)
Eighteen to twenty years ago (1997–1999), the “Laurisilva project” collected many caddisflies systematically and intensively from springs and streams in the laurel forests in the Madeira Archipelago. The Trichoptera fauna of Madeira has been well known for a long time, but unexpectedly this collection included a series of specimens belonging to a new species, which is described here as Synagapetus laurisilvanicus n. sp. This new species is related to the Madeiran endemic Synagapetus punctatus (Hagen 1859), but these two species are readily distinguished by their wing venation and several genital characters, especially by the morphology of the inferior appendages and the aedeagus.